Effects of German Language Teacher Professional Development on Pupils’ Learning Outcomes in Intercultural Competence - Ana Šenjug Golub (Center for Educational Policy Studies Journal)
The development of intercultural competence is increasingly being perceived as a key goal in today’s education. As a result of a strong emphasis on that competence in curricular documents, teachers are faced with demanding tasks. Confirming this, recent research in the field of intercultural competence in Croatian schools indicates the numerous difficulties teachers face in accomplishing the goal of developing their pupils’ intercultural competence. Teacher professional development can be crucial for a systematic approach to the development of learners’ intercultural competence. Therefore, the aim of this study was to determine whether teacher participation in a further professional development programme on the topic of intercultural competence can significantly affect the achievement of goals set in the current curricular documents on foreign language learning related to intercultural competence. The effects of the professional development programme were assessed by means of analysing learner outcomes in intercultural competence prior to and after teacher participation in the programme. A quasi-experimental pre-test-post-test design was used, and the achievements of 752 primary and lower secondary level pupils attending 4th and 8th grades were evaluated. The results confirmed that foreign language teacher professional development in the field of intercultural competence had positive effects on pupils’ learning outcomes, especially in the cognitive component of intercultural competence. This leads to the conclusion that it is necessary to motivate foreign language teachers to participate in such programmes. The results also indicate the necessity of placing particular emphasis on the problem of stereotypes and prejudices when designing such programmes.